Network Formation by Generative AI Assistant of Personal Adaptive Ethical Semantic and Active Ontology - Evgeniy Bryndin (Journal of Advanced Research in Education, 2025)
In the process of life, a person forms and develops a three-level adaptive, thinking and ethical spatial intelligence. Adaptive intelligence is formed and developed in the environment, forming a spatial adaptive ontology. Thinking intelligence is formed and developed by multimodal communication, learning, problem solving and decision making, forming a spatial semantic ontology. Ethical intelligence is formed and developed according to ethical values, forming spatial ethical value ontology. Three-level adaptive thinking ethical spatial ontology participates in decision-making in real time at every moment of human activation in space. Three-level adaptive thinking ethical spatial personal ontology of knowledge and skills can be formed by a generative AI assistant network learning. By forming three-level personal ontology, it will be possible to effectively and efficiently develop relevant and promising scientific research education. Preparing specialist for research activities, teaching his research skills and skills becomes the most important task of modern education. Training a specialist who can think creatively, independently find solutions in problem situations, navigate the information space is a priority in modern research education. Research scientific education helps to prepare qualified specialists capable of independent scientific activity and innovation, which is especially important in the context of a rapidly changing world and global challenges. Consequently, research education allows for the development of practically effective research activities based on the latest trends and discoveries in science, as well as the formation of fundamental science leading to new practical results.